Ki Hajar Dewantara’s "Guiding" Basic of Education at Muhammadiyah Alam Surya Mentari Elementary School - Kusuma, Anton Adi Suryo; Fahma, Naomi; Fauziyati, Endang; Harsono, Harsono; Musiyam, Muhammad (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
One of the national heroes who fought for education in Indonesia was Ki Hajar Dewantara. The various thoughts that Ki Hajar Dewantara contributed brought progress to education in Indonesia. The five basics of education, according to Ki Hajar Dewantara, encompass guiding, the nature of nature, the nature of the times, manners, and the among system. Many previous studies have discussed the “among system.” Therefore, in this study, the researchers aim to outline Ki Hajar Dewantara's "guiding" basics of education at elementary school. The method used in this research was qualitative with a case study approach. Data collection was carried out by observation, interviews, and documentation. Data analysis techniques employed the Milles and Huberman model, including data collection, data reduction, data presentation, and conclusions. The research findings demonstrated that Ki Hajar Dewantara’s educational concept of "guiding" at Muhammadiyah Alam Surya Mentari Elementary School could be seen from (a) the learning objectives, namely guiding the nature of students to become human beings with character by teaching honesty, good manners, and leadership; (b) the learning process, which guides each student to learn optimally according to each student's readiness, learning profile, and diverse interests by using various methods, media, and scaffolding in learning; and (c) habituation activities before learning, such as reading Qur’an, stretching, praying Dhuha in the congregation, and praying together.